RUANG HUNIAN DAN KREATIF ANAK-ANAK YATIM PIATU - Gavin Hanli Lim; Suwandi Supatra (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2023)
As of September 2021, the Ministry of Social Affairs received reports that the number of orphans had reached 28 thousand people which was caused by the main impact, namely Covid-19. The DKI Jakarta Provincial Government held a meeting and stated openly about the number of people who died of more than 13 thousand people and resulted in 9 thousand children in Jakarta becoming orphans or orphans. As orphans who are also affected by Covid-19, some have received assistance and have foster parents. But this does not mean that the problem has been solved. In terms of empathy with the suffering of orphans, emotional contagion will evoke an intense state within oneself, just as someone who is experiencing distress by softening the boundaries between himself and others. Modern empathetic architectural design focuses on design that engages the community. An understanding of how the built environment will have an impact on social change. Establish design with past and future societies in a close relationship. Orphans are included in the category of vulnerable children or children who need special protection (children in need of special protection). They are said to be neglected because their basic needs are not met spiritually, physically, or socially. The Covid-19 pandemic has had a huge impact on all sectors of life. The death toll from the corona virus is still falling to this day. Orphans often have stunted physical growth due to their inadequate nutritional needs. In addition to psychological barriers, orphans also experience emotional barriers. In healthy families, children will fear that their parents "disappear" in their lives. Orphans need a place where they can feel love and prosperity. This container adjusts to the daily life of orphans and ergonomics so that it can provide a sense of comfort and security with assurance. With containers and programs that are in accordance with activities, activities and needs, it is hoped that orphans can be free from feelings of loneliness, mental illness, depression and be replaced by a sense of family, live healthy and smart, and be wiser. Orphans need a place where they can feel love and prosperity. This container adjusts to the daily life of orphans and ergonomics so that it can provide a sense of comfort and security with assurance. With containers and programs that are in accordance with activities, activities and needs, it is hoped that orphans can be free from feelings of loneliness, mental illness, depression and be replaced by a sense of family, live healthy and smart, and be wiser. Keywords: empathy; empathy architecture; orphans; psychological Abstrak Hingga September 2021, Kementerian Sosial menerima laporan bahwa jumlah anak yatim piatu mencapai 28 ribu orang yang disebabkan oleh dampak utamanya yaitu Covid-19. Pemprov DKI Jakarta mengadakan rapat serta menyatakan secara terbuka tentang jumlah orang yang meninggal lebih dari 13 ribu jiwa dan mengakibatkan 9 ribu anak di Jakarta menjadi yatim atau yatim piatu. Sebagai anak yatim piatu yang juga terdampak covid-19 sebagian telah mendapatkan bantuan serta mempunyai orang tua asuh. Tetapi ini bukannya berarti bahwa persoalan telah selesai. Dalam empati kaitannya dengan kesusahan anak-anak yatim piatu, maka penularan emosi akan membangkitkan keadaan intens dalam diri seperti halnya seseorang yang mendapatkan kesusahan dengan cara memperlembut batasan antara dirinya dengan orang lain. Desain arsitektur empati modern memfokuskan pada desain yang melibatkan komunitas. Pemahaman bagaimana lingkungan bangunan akan memiliki dampak pada perubahan sosial. Menjalin desain dengan masyarakat masa lalu dan masa depan dalam suatu hubungan yang erat. Anak yatim piatu termasuk kategori anak rawan atau anak-anak yang membutuhkan perlindungan khusus (children in need of special protection). Mereka dikatakan terlantar karena tidak terpenuhi kebutuhan dasarnya baik secara rohani, jasmani, maupun sosial. Pandemi Covid-19 telah berdampak sangat besar dalam seluruh sektor kehidupan. Korban jiwa akibat virus corona itu pun masih terus berjatuhan hingga saat ini. Anak yatim piatu sering terhambat pertumbuhan fisiknya karena kebutuhan gizi yang kurang. Selain hambatan psikologis, anak-anak yatim piatu juga mengalami hambatan emosional. Dalam keluarga yang sehat, anak-anak akan merasa takut apabila orang tua mereka "menghilang" dalam kehidupan mereka. Anak-anak yatim piatu membutuhkan sebuah wadah dimana dirinya dapat merasakan kasih sayang dan sejahtera. Wadah ini menyesuaikan dengan keseharian anak-anak yatim piatu dan ergonomi agar dapat memberikan rasa nyaman dan aman dengan terjamin. Dengan wadah serta program yang sesuai dengan kegiatan, aktivitas dan kebutuhan diharapkan anak-anak yatim piatu dapat bebas dari rasa kesepian, penyakit mental, depresi dan digantikan menjadi rasa kekeluargaan, hidup sehat dan pintar, dan lebih bijaksana.